The age of innocence [videorecording (DVD)] - Scorsese, Martin; Scorsese, Martin; Day-Lewis, Daniel; Pfeiffer, Michelle, 1957-; Ryder, Winona, 1971-; Chaplin, Geraldine, 1944-; Wharton, Edith, 1862-1937 (Columbia Pictures Industries : Distributed byColumbia TriStar Home Video, 2001)
In New York City in the 1870s, a rigid social code governs how people talk, walk, meet, part, dine, earn their livings, fall in love, and marry. Not a word of the code is written down anywhere, but these people have been studying it since they were born. In this elegant milieu, marriages, like treaties between nations, exist to provide for the orderly transmission of wealth; scions of old and rich families understand that their personal desires have no place in the design. One such is Newland Archer, engaged to marry pretty young May Welland. When he becomes entranced with May's cousin Ellen, the notorious Countess Olenska, every member of that class mobilizes to prevent Archer from doing anything that threatens their needs.